2023
DOI: 10.1038/s41392-023-01442-3
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways in cancer metabolism: mechanisms and therapeutic targets

Abstract: A wide spectrum of metabolites (mainly, the three major nutrients and their derivatives) can be sensed by specific sensors, then trigger a series of signal transduction pathways and affect the expression levels of genes in epigenetics, which is called metabolite sensing. Life body regulates metabolism, immunity, and inflammation by metabolite sensing, coordinating the pathophysiology of the host to achieve balance with the external environment. Metabolic reprogramming in cancers cause different phenotypic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 416 publications
0
21
0
Order By: Relevance
“…Additionally, FA species with fully saturated lipid (e.g., FA16:0, FA18:0) are localized to the peripheral microareas (e.g., hybrid hyperplastic and glandular cavity areas) of tumors in early stage. These results are in most cases correlated with the reduction of the membrane permeability to drugs. , Rysman et al reported that the cancerous and necrotic areas containing upregulated FA species with various degrees of unsaturation have been shown to occur during tumor progression. This situation could improve the fluidity of the cellular membrane, which is necessary for proliferation and invasion of cancer cells …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, FA species with fully saturated lipid (e.g., FA16:0, FA18:0) are localized to the peripheral microareas (e.g., hybrid hyperplastic and glandular cavity areas) of tumors in early stage. These results are in most cases correlated with the reduction of the membrane permeability to drugs. , Rysman et al reported that the cancerous and necrotic areas containing upregulated FA species with various degrees of unsaturation have been shown to occur during tumor progression. This situation could improve the fluidity of the cellular membrane, which is necessary for proliferation and invasion of cancer cells …”
Section: Resultsmentioning
confidence: 93%
“…FA species (20:2/3) are produced by the synthesis pathway from essential linoleic acids (Omega 6) [FA(18:2)] and α-linoleic acids (omega 3) [FA(18:3)] to arachidonic acid [FA(20:4)]. As the intermediate species of FA synthesis, they are characterized as nonproductive accumulation. , Upregulated FA­(20:2/3) during tumor progression demonstrates a significant preference for de novo lipid synthesis. During tumor progression, various cancer cells use de novo synthesized FAs to produce excessive biomass for cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The receptors for sensing metabolites, the associated signaling pathways, and the crosstalk with epigenetic pathways have been investigated. [ 23,108,109 ] There is potential to integrate metabolomics and/or in vivo isotope infusion with histological and molecular studies to map distinct metabolic domains and correlate them with specific combinations of mutations or microenvironmental influences. This paves the way for the future development of delivery systems based on metabolic features.…”
Section: Discussionmentioning
confidence: 99%
“…A series of signaling pathways (Fig. 4 ) collectively regulate biological processes in human malignancies and are associated with the proliferation, invasion and therapeutic resistance of cancer cells [ 94 ]. The expression of signaling pathway components can be modulated by miRNAs through miRNA–mRNA binding, typically to miRNA target sites in the mRNA 3’-UTR [ 40 , 95 ].…”
Section: Mechanisms Of Drug Resistance In Ovarian Cancermentioning
confidence: 99%